Epidemiologic Study of Retinoblastoma in Recife, Pernambuco - Brazil: January 1985 - July 1997 - Abreu,Armando Anderson (1999)
Background: Retinoblastoma is by far the most frequent malignant intraocular tumor of childhood. This study was performed to characterize the clinical, diagnostic, treatment and prognostic aspects in patients with retinoblastoma in three reference centers for this pathology in the city of Recife, Pernambuco - Brazil. Methods: A consecutive series of 85 patients with retinoblastoma was reviewed. The authors selected 66 patients (77.6%) that fulfilled the inclusion criteria for these study. Results: Of a total of 66 patients with retinoblastoma, 4.5% had a previous history of the disease in the family. Males were more affected than females at a ratio (male/female) of 1.12. The mean age of appearance of the first symptoms was 23.8 months, with leukocoria and ocular hyperemia being the most frequent. The mean age at time of diagnosis was 31.7 months and for surgical treatment 32.8 months. The right eye was affected in 42.4% of the cases and the left was involved in 37.9% of cases. The tumor was unilateral in 80.3% and bilateral in 19.7% of the cases. There was extraocular involvement in 62.1%, and it was intraocular in 37.9% of the patients. Treatment was surgery combined with chemotherapy in 47.0% of the patients. 27.3% of the patients died and 19.7% abandoned the treatment. Conclusions: The data on the epidemiology of retinoblastoma found in our city resembles that of other developing countries, concerning the epidemioloy of retinoblastoma.